Letter: systematic review with meta‐analysis on the impact of functional cure on clinical outcomes in patients with chronic hepatitis B—authors' reply. Issue 5 (9th February 2022) - Vittal, Anusha; Sharma, Disha; Hu, Alvin; Majeed, Nehna A.; Auh, Sungyoung; Ghany, Marc G.
LINKED CONTENT: This article is linked to Vittal et al papers. To view these articles, visit https://doi.org/10.1111/apt.16659 and https://doi.org/10.1111/apt.16758